New approach to the Lithuanian road classification based on worldwide experience - Vitkienė, Jūratė; Puodžiukas, Virgaudas; Žilionienė, Daiva (International Conference “Environmental Engineering”, 2017)
Road classification and road hierarchy are essential steps making sure that roads are designed and used properly. Road classification is an approach, to sort them into a small number of groups or classes, and then assigns the roads in a network to one or more of these groups. There are many ways to classify roads. One of them is regarding road hierarchy (or more specifically, functional road hierarchy). The efficiency and effectiveness of the road network directly impact economic growth and societal development. Economically, it is important through classification of roads to represent every road function, as it can enhance the delivery of goods efficient and effective. Arterial roads of a higher class significantly influence economic development by providing the main route of fright transportation and services, as well as significantly influence societal development as it provides a safe, effective and efficient route to travel on. At the same time, the high volume of traffic-related accidents calls for a road network that is safe for all road-users. It is known that the physical road network affects traffic and driver behaviour, and this in turn directly influences energy consumption and the environmental impacts associated with the emissions thereof. In this article review at road classification and road hierarchy of worldwide. It concludes with some comments on the current Lithuanian situation. It can be achieved in Lithuania to make influences to road safety, speed regulation, driver behaviour, traffic studies and accessibility to services.